SCIENCEDIRECT: ESSENTIAL RESEARCH FOR DEVELOPING READING COMPREHENSION IN NARRATIVE QUALITATIVE RESEARCH - Aldina, Aldina Kamila; Ferdiyanto, Feri; Islam, Raudhatul (English Language Teaching Prima Journal (ELT), 2025)
This study aimed to determine the effectiveness of ScienceDirect in improving the English reading skills of students at Zainul Hasan Genggong Islamic University with a focus on text comprehension and reading skills. Using a narrative qualitative approach, this study collected data through observation, interviews, and documentation from students who used ScienceDirect. The results showed that the use of ScienceDirect had a significant effect on students' English reading skills, with better text comprehension abilities compared to conventional methods. This study concluded that ScienceDirect was effective in improving students' English reading skills, so it could be an alternative to innovative and effective learning to improve English reading skills and achieve better learning objectives. Thus, this study contributed to the development of more effective and innovative English learning methods and provided recommendations for educators and researchers to utilize ScienceDirect as a valuable learning resource. This study was also expected to be a reference for further research related to the use of technology in English learning.